Specialization-generalization trade-off in a Bradyrhizobium symbiosis with wild legume hosts - Ehinger, Martine (BioMed Central, 2014)
BACKGROUND: Specialized interactions help structure communities, but persistence of specialized organisms is puzzling because a generalist can occupy more environments and partake in more beneficial interactions. The “Jack-of-all-trades is a master of none” hypothesis asserts that specialists persist because the fitness of a generalist utilizing a particular habitat is lower than that of a specialist adapted to that habitat. Yet, there are many reasons to expect that mutualists will generalize on partners. Plant-soil feedbacks help to structure plant and microbial communities, but how frequently are soil-based symbiotic mutualistic interactions sufficiently specialized to influence species distributions and community composition? To address this question, we quantified realized partner richness and phylogenetic breadth of four wild-grown native legumes (Lupinus bicolor, L. arboreus, Acmispon strigosus and A. heermannii) and performed inoculation trials to test the ability of two hosts (L. bicolor and A. strigosus) to nodulate (fundamental partner richness), benefit from (response specificity), and provide benefit to (effect specificity) 31 Bradyrhizobium genotypes. RESULTS: In the wild, each Lupinus species hosted a broader genetic range of Bradyrhizobium than did either Acmispon species, suggesting that Acmispon species are more specialized. In the greenhouse, however, L. bicolor and A. strigosus did not differ in fundamental association specificity: all inoculated genotypes nodulated both hosts. Nevertheless, A. strigosus exhibited more specificity, i.e., greater variation in its response to, and effect on, Bradyrhizobium genotypes. Lupinus bicolor benefited from a broader range of genotypes but averaged less benefit from each. Both hosts obtained more fitness benefit from symbionts isolated from conspecific hosts; those symbionts in turn gained greater fitness benefit from hosts of the same species from which they were isolated. CONCLUSIONS: This study affirmed two important tenets of evolutionary theory. First, as predicted by the Jack-of-all-trades is a master of none hypothesis, specialist A. strigosus obtained greater benefit from its beneficial symbionts than did generalist L. bicolor. Second, as predicted by coevolutionary theory, each test species performed better with partner genotypes isolated from conspecifics. Finally, positive fitness feedback between the tested hosts and symbionts suggests that positive plant-soil feedback could contribute to their patchy distributions in this system.